A emergência do conceito da interculturalidade no ensino e aprendizagem de língua estrangeira - Galelli, Cinthia Yuri [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the last years, we can observe the increasing use of intercultural(ity) terms in Educational Discourses, especially those dealing in Foreign Language (LE in Portuguese). This term comes, for some time, gaining space in the European Educational Documents as well in the South American ones. It is considerable in Brazil, for example, the concern about the development of a intercultural dimension in relation to the National Curriculum Parameters (PCN in Portuguese), the Curricular Guidelines, the textbooks and countless academic researches published about teaching and learning a Foreign Language. Thus, we can say that interculturality is the Discursive Order. In light of this, this research aims to verify how the discourse is based on the interculturality in the teaching of Foreign Languages through the analysis instrument undertaken by Michel Foucault, named Archeology. In other words, we aim to answer the question: what are the emergency conditions of the interculturality concept in the teaching and learning of foreign languages? To answer this question, it was done an analysis about the enunciative functions, purposing to describe materiality, the subject and the statement of the Official Documents statements related to education published by the Council of Europe and the Education Ministry in Brazil. In addition, we mapped the correlations established between the statements of interculturality in the teaching of foreign language and the statements of associated areas as Linguistics and Social Sciences. Researches show that the enunciation operation about interculturality exists and it has success because we have subjects able to enunciate. This occurs due to the authority of these subjects in relation to language teaching, as renowned linguists or governmental organization; a statement based on a materiality with regularities and deletions discursive that produce truth effects, supported on a memory network, and associated areas, such...

Pode-se observar nos últimos anos o crescente uso dos termos intercultural(idade) nos discursos educacionais, sobretudo os que tratam de língua estrangeira (LE). Esse termo vem, há algum tempo, ganhando espaço tanto nos documentos educacionais europeus, quanto nos da América do Sul. É notável no Brasil, por exemplo, a preocupação pelo desenvolvimento de uma dimensão intercultural nos Parâmetros Curriculares Nacionais (PCNs), nas Orientações Curriculares, nos livros didáticos e nas inúmeras investigações acadêmicas publicadas sobre ensino e aprendizagem de LE. Assim, podemos afirmar que a interculturalidade está na ordem do discurso. Diante desse acontecimento, este trabalho objetiva verificar como se instaurou o discurso sobre a interculturalidade no ensino de línguas estrangeiras a partir do instrumento de análise empreendido por Michel Foucault, denominado arqueologia. Em outras palavras, buscamos responder à seguinte pergunta: quais são as condições de emergência do conceito de interculturalidade no ensino e aprendizagem de línguas estrangeiras? Para responder a essa questão, empreendeu-se uma análise das funções enunciativas, buscando descrever as materialidades, o sujeito e o referente dos enunciados dos documentos oficiais de educação publicados pelo Conselho da Europa e pelo Ministério da Educação do Brasil. Além disso, mapeamos as correlações estabelecidas entre os enunciados da interculturalidade no ensino de LE com enunciados de campos associados como a linguística e as ciências sociais. Os estudos demonstram que o funcionamento enunciativo sobre a interculturalidade existe e tem êxito porque temos sujeitos aptos a enunciá-los pois são portadores de autoridade em relação ao ensino de línguas, como linguistas renomados ou organização governamental; um referente que se apoia em uma materialidade com regularidades e apagamentos discursivos que produzem, apoiados em uma rede de memórias...
Keywords: Ensino; Linguas - Estudo e ensino; Análise do discurso; Relações culturais; Teaching